Intracranial Pressure–Guided Shunt Valve Adjustments with the Miethke Sensor Reservoir - Antes, Sebastian; Stadie, Axel; Müller, Simon; Linsler, Stefan; Breuskin, David; Oertel, Joachim (World Neurosurgery, 2018)
Background Telemetric intracranial pressure (ICP) monitoring seems to be a promising therapy-supporting option in shunt-treated patients. Benefits become obvious when headaches are unspecific and clinical symptoms cannot be related to possible overdrainage or underdrainage. In this study, we evaluated a new telemetric device to individually adjust shunt valves according to ICP measurements. Methods Between December 2015 and November 2016, 25 patients with suspected suboptimal shunt valve settings underwent insertion of a telemetric ICP sensor (Sensor Reservoir; Christoph Miethke, Potsdam, Germany). Over a 1-year period, a total of 183 telemetric ICP measurements and 85 shunt valve adjustments were carried out. Retrospective statistic analyses focused on valve adjustments, ICP values, and clinical outcomes. Results ICP-guided valve adjustments positively changed the clinical state in 18 out of 25 patients. Clinical improvement over time was associated with significant changes of the valve settings and ICP values. Interestingly, a therapeutically normalized ICP profile was not automatically associated with clinical improvement. Conclusions The Sensor Reservoir is an important and valuable tool for shunt-treated patients suffering from drainage-related problems. The possibility to simultaneously recognize and solve shunt problems represents the decisive advantage. Nevertheless, measurements with the Sensor Reservoir did not allow for the determination of default valve settings or universal target ICP values.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Hydrocephalus; Intracranial pressure; Sensor reservoir; Shunt; Telemetric ICP measurement; Telemetry